Inhibition effect of zinc in wastewater on the N2O emission from coastal loam soils. Issue 1 (15th March 2017) - Huang, Yan; Ou, Danyun; Chen, Shunyang; Chen, Bin; Liu, Wenhua; Bai, Renao; Chen, Guangcheng
Abstract: The effects of zinc (Zn) on nitrous oxide (N2 O) fluxes from coastal loam soil and the abundances of soil nitrifier and denitrifier were studied in a tidal microcosm receiving livestock wastewater with different Zn levels. Soil N2 O emission significantly increased due to discharge of wastewater rich in ammonia (NH4 + -N) while the continuous measurements of gas flux showed a durative reduction in N2 O flux by high Zn input (40 mg L − 1 ) during the low tide period. Soil inorganic nitrogen concentrations increased at the end of the experiment and even more soil NH4 + -N was measured in the high-Zn-level treatment, indicating an inhibition of ammonia oxidation by Zn input. Quantitative PCR of soil amoA, narG and nirK genes encoding ammonia monooxygenase, nitrate reductase and nitrite reductase, respectively, showed that the microbial abundances involved in these metabolisms were neither affected by wastewater discharge nor Zn contamination. Highlights: Wastewater input enhances soil N2 O flux with nitrification as principal mechanism. High Zn level reduces the enhancement of N2 O flux by wastewater input. More ammonia in Zn-affected soil indicates less ammonia oxidation. Changes in abundances of functional microbe do not explain the Zn inhibition effect.